Effects of Lactobacillus probiotics supplemented with concentrate feed on growth performance, carcass characteristics, and caecal microflora of RIR chickens - Kibrnesh Tegenaw Tsega; J. Maina Kagira; Nega Berhane Tessema; Shewangzaw Addisu Mekuria (Cogent Food & Agriculture)
Probiotic use is suggested as an alternative to antibiotics when the treatment of poultry gastrointestinal tract microbiota through antibiotic use has been banned in some countries. The objective of this study was to evaluate the effect of previously isolated Lactobacillus salivarius CEL1 and Lactobacillus reuteri CEC3 probiotics on the growth performance, caecal microbial population, and carcass weight of Rhode Island Red (RIR) male chickens. A total of 72, day-old RIR male chicks were randomly assigned into three experimental treatment groups in triplicate. The treatment groups were the control, L. salivarius CEL1 and L. reuteri CEC3. The control group was fed basal chicken feed, and 1 × 108 cfu of L. salivarius CEL1 and L. reuteri CEC3 cultures were added to the feed for the L. salivarius CEL1 and L. reuteri CEC3 groups, respectively. The Lactobacillus, total aerobic bacteria, and Escherichia coli populations in the ceca were also determined. Compared to the control group, supplementation of L. salivarius CEL1 and L. reuteri CEC3 significantly (p < 0.05) increased body weight and body weight gain and the number of E. coli and total aerobic bacteria in the cecum of chickens were reduced. In addition, L. salivarius CEL1 and L. reuteri CEC3 supplementation resulted in significantly high dressing and internal organ weights. However, there were no statistically significant differences in feed intake and feed conversion efficiency between treatments at 42 days of rearing. This study revealed that L. salivarius CEL1 and L. reuteri CEC3 could be considered good potential probiotics for chickens.